Validation of the Exhaled Breath Temperature Measure: Reference Values in Healthy Subjects - Carpagnano, Giovanna E; Foschino-Barbaro, Maria P; Crocetta, Corrado; Lacedonia, Donato; Saliani, Valerio; Zoppo, Luigi Davide; Barnes, Peter J (Chest, 2017)
Exhaled breath temperature (EBT) is a new noninvasive method for the study of inflammatory respiratory diseases with a potential to reach clinical practice. However, few studies are available regarding the validation of this method, and they were mainly derived from small, pediatric populations; thus, the range of normal values is not well established. The aim of this study was to measure EBT values in an Italian population of 298 subjects (mean age, 45.2 ± 15.5 years; 143 male subjects; FEV , 97.2% ± 5.8%; FVC, 98.4% ± 3.9%) selected from 867 adult volunteers to define reference values in healthy subjects and to analyze the influence of individual and external variables on this parameter. EBT was measured with an X-halo PRO device to different ambient temperature ranging from 0°C to 38°C. We report reference values of EBT in healthy white subjects who had never smoked. EBT values were strongly influenced by the external temperature and to a lesser extent according to sex. In a large population of healthy subjects who never smoked, these data provide reference values for measuring EBT as a basis for future studies. Our results are contribute to the promotion of EBT from "bench" to "bedside."